Ibero-American government communication in the face of the first local case of SARS-CoV-2 - Mena Young, Margoth (2025)
Introduction: In March 2020, the global spread of the novel coronavirus SARS-CoV-2 posed an unprecedented challenge to governments and public communication. Upon the detection of the first confirmed case within their territories, Ibero-American countries faced the urgent need to inform their citizens amidst a context of heightened uncertainty and concern. Objective: This article aims to analyse the official communication strategies employed by the governments of Argentina, Brazil, Chile, Colombia, Costa Rica, Spain, Mexico, and Panama when announcing their first confirmed case of COVID-19. The focus lies on the messages disseminated through press releases and social media platforms, as well as the public's responses to these communications. Method: A qualitative analysis was conducted on the press releases issued by the governments of the selected eight countries. Additionally, 16 official posts from Facebook and Twitter (8 from each platform) were examined, along with 567 citizen comments (360 on Facebook and 207 on Twitter), to identify communication patterns and public reactions. Results: The findings reveal a chaotic scenario in which governments faced considerable challenges in delivering clear and effective messages. While the communication strategies exhibited similarities across countries, sociopolitical and cultural contexts significantly influenced public perception. Citizen responses on social media reflected widespread dissatisfaction and unmet expectations, such as a lack of clarity and sensitivity in the messaging. This study underscores the need to strengthen governmental health communication by incorporating risk management, scientific dissemination, active listening, and contextually sensitive approaches. Enhancing these practices is crucial for addressing future public health emergencies effectively.